Knowledge on postpartum type-2 diabetes mellitus screening among pregnant women with gestational diabetes mellitus in Malaysia - Minhat, Halimatus Sakdiah; Thangarajah, Puganeswary; Ahmad, Norliza (Academy of Family Physicians of Malysia, 2022)
Introduction: Despite the effectiveness of postpartum type 2 diabetes mellitus (T2DM) screening to detect and manage T2DM among women with a history of gestational diabetes mellitus (GDM), the uptake remains low, indicating the potentially low level of relevant knowledge. This study aims to identify the prevalence of postpartum T2DM screening and its associated factors. Methods: A cross-sectional study was conducted involving 116 pregnant women with GDM who attended antenatal care follow-up at government health clinics in Seremban District, Negeri Sembilan. Multistage cluster sampling was performed to recruit the respondents from 6 mukims and 10 public health clinics. The data were collected using a validated and pre-tested questionnaire, with Cronbach’s alpha values ranging from 0.81 to 0.95 for each section of the questionnaire. Data were collected through face-to-face interviews during the respondents’ routine antenatal follow-ups for blood sugar monitoring. Results: Poor knowledge on postpartum T2DM screening (55.2%) was observed, which was significantly predicted by low educational level (AOR = 6.898, 95% CI 3.62–9.055) and low self-efficacy (AOR =17.905, 95% CI 5.470–58.611). Conclusion: Most of the respondents had poor knowledge regarding postpartum T2DM screening, which was predicted by low education and self-efficacy. The findings highlight the need for continuous education and health promotion during antenatal follow-up targeting women with GDM with low self-efficacy and education level in order to ensure better adherence to screening.